Measurement of spring constant by means of Arduino: A STEM teaching proposal - Erol, Mustafa; Navruz, YiÄŸit Efe (Universitas PGRI Kanjuruhan Malang, 2023)
This study advances a STEM teaching proposal and aims to determine spring constant of a spring pendulum by means of an Arduino microprocessor. The measurements are managed by simply letting the spring pendulum to oscillate freely and recording the distance perceived by the distance sensor-Arduino system as a function of time. The mean periods are estimated by using displacement-time plots of the harmonic motion and the results are used to estimate the spring constant. The spring constant is also determined conventionally by employing Hooke's law a number of times. The relative error rate between the two results is found to be about % 6.00 which is pretty acceptable. This approach is important in the sense that it is inexpensive and also encourages students to learn how to use the Arduino microprocessor. The approach adds to physics education efforts due to creating an enjoyable and beneficial teaching-learning environment.